Arohynapene A Produced by Penicillium steckii JB-NW-2-1 Isolated from Avicennia marina (Forssk.) Vierh and Its Cytotoxic Activities - Yeni Mulyani; Wahyu Syafriansyah; Asri Peni Wulandari; Azmi Azhari; Sari Purbaya; Aprilia Permata Sari; Galih Bayu Pratama; Fajar Fauzi Abdullah; Kindi Farabi; Unang Supratman; Yoshihito Shiono (Universitas Gadjah Mada, 2024)
Mangrove-associated endophytic fungi are producers of secondary metabolites in unique and diverse structures with interesting biological activities such as antiviral, antifungal, antibacterial, anti-inflammatory, and cytotoxic agents. Endophytes play an important role in the physiological activities of the host plants, influencing the improvement of resistance to stress, insects, nematodes, and diseases. In this study, arohynapene A, a polyketide compound, was successfully isolated from the mangrove-derived fungus Penicillium steckii JB-NW-2-1 obtained from mangrove plant Avicennia marina (Forssk) Vierh. The structure was determined by a spectroscopic method including IR, MS, 1D-, and 2D-NMR techniques. This compound was evaluated for cytotoxic activities using resazurin assay against four cancer cells, HeLa cervical, MCF-7 breast cancer, B16-F10 melanoma, and A549 lung adenocarcinoma. The results showed no significant activities against all cancer cells tested (IC50 > 500 µM).